Long Period Fiber Grating Fabrication by Two-Step Infrared Femtosecond Fiber Laser Exposure - Cong Zhang; Li Cheng; Songnian Fu; Ming Tang; Deming Liu (IEEE Photonics Journal, 2017)
We develop a two-step infrared (IR) femtosecond fiber laser exposure technique to flexibly fabricate long period fiber gratings (LPFGs) with a high peak band-rejection efficiency of 35.4 dB, insertion loss of 4.36 dB, and 3 dB bandwidth of 13 nm. First, we etch periodic corrugations via IR femtosecond laser in the cladding of standard single mode fiber, leading to efficient laser beam-focusing on the cladding as well as stress-optic refractive index (RI) modulation. Then, we carry out femtosecond fiber laser irradiation under the corrugations, to further introduce RI modulation within fiber core. We experimentally investigate the impacts of fabrication parameters including laser focus location and individual exposure time with respect to the transmission spectra of LPFGs. The fabricated LPFG has a temperature coefficient of 114 pm/°C and a polarization dependent loss of 1.78 dB, which may find useful applications in sensors.